Study of the behavior of Long Tailed Monkeys (Macaca fascicularis) in the Jumprit Indigenous Forest - Fitriani, Robithoh Ranitia; Wijayanti, Erna (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2024)
Research on the behavior of long-tailed monkeys (Macaca fascicularis) was conducted in the Jumprit Customary Forest located on the slopes of Mount Sumbing, Jumprit Village, Ngadirejo District, Temanggung Regency. This study aims to determine the daily behavior of long-tailed monkeys in the Jumprit Customary Forest. This research is included in the type of exploratory descriptive research with direct observation into the field. The method used in the preliminary research was in the form of the Ad Libitum Sampling method, while in the main study the Scan Sampling method was used by observing behavior in a small population of long-tailed monkeys (Macaca fascicularis). Data collection was carried out for 7 days at time intervals between 08.00 to 16.00. The observed data is then processed descriptively, qualitatively and quantitatively. The results of the observations obtained behavioral activity of long-tailed monkeys (Macaca fascicularis) which were observed consisting of 8 types of behavior, namely foraging behavior, moving, playing, social interaction, inactivity, vocalizing, mating and mother and child interaction. Both places of observation have different intensities of behavioral activity. Place 1 (forest border with highway) shows the intensity of long-tailed monkey behavior that is lower than the behavioral intensity of long-tailed monkeys in place 2 (Umbul Jumprit).